Productivity of Timberjack 350A and Tree Farmer C5D skidders in group-selective cutting and assortment method (Journal of Forestry, 2024)
In the forestry of Bosnia and Herzegovina winching and skidding of wood assortments is usually done with skidders equipped with a cable winch. This is one of the most expensive and technologically challenging activities of forest exploitation. It is of great importance to analyse the productivity of these machines as often as possible, to obtain the most efficient solutions in the forest harvesting technologies and to increase the profitability of harvesting operations. In this research, the productivity of two cable skidders, Timberjack 350A and Tree Farmer C5D, were analysed to determine their productivity and applicability in conditions of group-selective forest management and motor-manual assortment harvesting method. The goal was also to investigate how mobile Android application AlpineQuest can simplify field data collection during a work study. The results of this research showed that older-generation skidders could be partially competitive with new-generation skidders when it comes to productivity, but for credible conclusion much more detailed investigation should be done. However, there are also many other features, such as ergonomic, ecological and some at first glance invisible technological changes that give the newer skidders a significant advantage. What is a big challenge for local forestry companies is that the official norms that have been used for a long time have been overcome, and they provide completely unreliable data about the time required for the execution of work, from which it follows that the accuracy of the economic plan is also questionable. Using the AlpineQuest application in data collection during the time and work-study has proven to be very successful. It found its greatest use in measuring winching and skidding distances, but it also generally facilitated workers’ orientation and movement in the area.